Perilaku Menolong Relawan Spontan Bencana Alam - Masitha Hanum Utomo; Wenty Marina Minza (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
The vulnerable conditions of Indonesia, especially Yogyakarta, to natural disastersled a lot of volunteers who want to help the survivor. Many of volunteers joined the socialcommunity or formal organization, but many of them do not belong to any social communityor organization and does not have the ability to handle the condition of natural disaster stillhelp the victims. These individuals referred as spontaneous volunteers. The aim of this studyis to determine the helping behavior conducted by spontaneous volunteers. The approachused in this study is qualitative specifically phenomenology. Data was collected by a semi-structured in-depth interview. Informants of this study consisted of three individuals, two ofthem was volunteered when the eruption of Mount Merapi occurred in 2010, and the otherone was volunteered in Banjarnegara’s landslide in 2014. Result showed that there arechanges of helping behavior from spontaneous to formal planned form of helping. There arealso several factors that encourage or inhibit their helping behavior.